2015
DOI: 10.2320/matertrans.m2014369
|View full text |Cite
|
Sign up to set email alerts
|

Flotation Behavior of Arsenopyrite and Pyrite, and Their Selective Separation

Abstract: This study investigated the effect of pH and pulp potential (E H ) on the floatability of arsenopyrite and pyrite, which are single minerals, in Hallimond tube, by using xanthate as a collector. On this basis, the study further investigated the selectivity index of arsenopyrite and pyrite, using a mixed sample of arsenopyrite and pyrite. To examine the flotation behavior of each mineral by pH change, flotation was carried out at pH 4 and pH 10. The test results showed arsenopyrite had higher floatability at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…By adding polymer molecules, also termed as a depletion agent or a depletant, we can increase the attractive interaction between a mineral particle and a bubble. ((Zn,Fe)S)) [10,20,[23][24][25]. These studies showed that sulfide minerals could provide better floatability in certain oxidation and reduction potential ranges by adjusting the solution pH, at which elemental sulfur forms a hydrophobic surface of sulfide minerals.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…By adding polymer molecules, also termed as a depletion agent or a depletant, we can increase the attractive interaction between a mineral particle and a bubble. ((Zn,Fe)S)) [10,20,[23][24][25]. These studies showed that sulfide minerals could provide better floatability in certain oxidation and reduction potential ranges by adjusting the solution pH, at which elemental sulfur forms a hydrophobic surface of sulfide minerals.…”
Section: Introductionmentioning
confidence: 93%
“…During this process, a collector is used to impart hydrophobicity to desired mineral particles; these hydrophobic particles are then better attached onto the surface of a bubble, leaving undesired particles in the bulk solution. Among these collectors is xanthate, which is a typical collector used for sulfide minerals and for oxide minerals after the sulfidization process [7][8][9][10]. Although this collector has been exploited extensively over the last several decades, a reduction in its use is desired because it is environmentally harmful [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flotation is a physico-chemical separation technique for particles and it has been used extensively for a wide range of mineral processes [1][2][3][4][5]. Although it is useful and powerful, flotation involves extremely complicated dynamic processes with various phase components (gas, liquid and solid) under flow; examples include the attachment of solid minerals to gas bubbles, the mixing of solid minerals under vigorous liquid flows, the formation of gas bubbles and the motion of bubbles due to buoyant force; none of which are completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 shows that SBX rendered the zeta potential of arsenopyrite more negatively. When xanthate ions were oxidized to dixanthogen on the arsenopyrite surface, negative zeta potential increased [36]. With SH, the zeta potential of arsenopyrite decreased sharply over the entire pH range.…”
Section: Flotation Separation Of Mixed Mineralsmentioning
confidence: 99%